Temperature Effects on Leaf and Epiphyte Photosynthesis, Bicarbonate Use and Diel O2 Budgets of the Seagrass Zostera marina L. - Hansen, Aske Bang; Pedersen, Anne Sofie; Kühl, Michael; Brodersen, Kasper Elgetti (Frontiers in Marine Science, 2022)
Ocean warming along with nutrient enrichment are major stressors causing global seagrass decline. While the effects of global warming on metabolic parameters in seagrasses are well described, the effect of increasing temperature on the epiphytic overgrowth of seagrass leaves and the consequences for the seagrass plant are poorly understood. Here, we investigated the effects of elevating temperature on the photosynthetic efficiency of the seagrass species Zostera marina L. and its associated epiphytes, to explore how ocean warming might affect epiphytism in seagrasses. Gas exchange and final pH measurements on bare seagrass leaves, leaves with epiphytes, and epiphytes separated from seagrass leaves were used to quantify photosynthesis and respiration rates, and the inorganic carbon extraction capacity of leaves and epiphytes as a function of photon scalar irradiance and temperature (12, 17, 22, and 27°C). Seagrass without epiphytic biofilm had a high ability to exploit the incoming irradiance regardless of the light intensity and temperature, shown as continuously high light use efficiency and maximum net photosynthesis rates. The presence of epiphytic biofilm on the seagrass leaves impaired plant photosynthesis by increasing light requirements and reducing the photosynthetic efficiency (especially at 27°C). Epiphytes showed the lowest respiration rates in darkness and had the highest oxygen surplus over diel cycles up to 22°C, whereas bare leaves had the highest diel oxygen surplus at 27°C. Both bare leaves and epiphytes lost the ability to utilize bicarbonate at 27°C, and epiphytes also did not show use of bicarbonate at 12°C. Our results indicate a competitive advantage for epiphytes in cold CO2-rich environments, whereas seagrass with bare leaves could be less affected under elevated seawater temperatures.